COMMUNITY BASED AGRO-TOURISM DEVELOPMENT STRATEGY FOR SUMBER ARUM VILLAGE, SONGGON, BANYUWANGI - Adetiya Prananda Putra; Firda Rachma Amalia; Sari Wiji Utami (Pusat Penelitian dan Pengabdian kepada Masyarakat (P3M) Politeknik Negeri Bali, 2019)
The purpose of this study was to identify superior commodities and prospective tourist attractions that support the development of agro-tourism oriented to the potential of Sumber Arum village. Besides, this study also aims to develop agro-tourism development strategies based on community based tourism that can be applied in the development of agro-tourism in Sumber Arum village. This research used a case study approach with Sumber Arum village as the object of research. Analysis of determining superior commodities and tourist attractions used exponential comparison (MPE) method. The arrangement of development strategies is based on community based tourism using analysis of IFE, EFE, IE, SWOT, and AHP. The results showed that water lettuce, celery, and ferns were superior commodities for the development of agro-tourism. Priority development strategies that could be recommended to the Sumber Arum village to develop agro-tourism based on community based tourism are (1) utilizing the potential of agricultural land into agro-tourism zoning, (2) providing training about basic tourism to agro-tourism society,(3) collaborating with tourism industry stakeholders to introduce agro-tourism destinations, (4) creating community-based agro-tourism brands, and (5) increasing community involvement for renewal of agro-tourism products.